Governance Solutions to the Tragedy of the Commons That Marine Plastics Have Become - Vince, Joanna; Hardesty, Britta D. (Frontiers in Marine Science, 2018)
Plastic pollution has become the new millennium’s tragedy of the commons. This is particularly true with the marine debris plastic pollution issue, which has seen significant global interest recently. There is long-standing acknowledgement of the difficulty in managing the commons, with regulations, economic and market based instruments and community-based solutions all having a role to play. We review the global plastic pollution issue in the context of governance and policy, providing examples of successes, opportunities and levers for change. We discuss the role of regulation, public perception and social license to operate (SLO) in managing waste that enters the ocean. We argue that while plastic pollution is a tragedy, there are many opportunities for reduction, management, and changes to the global community’s relationship with plastic.